2010
DOI: 10.1002/app.32619
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, crystallization, and properties of biodegradable poly(butylene adipate‐co‐terephthalate)/organomodified montmorillonite nanocomposites

Abstract: Intercalated and exfoliated nanocomposites of biodegradable poly(butylene adipate-co-terephthalate) (PBAT) and Cloisite 30B (C30B) were fabricated by a solution-casting method to study the effects of the clay loading on the crystallization behavior, thermal stability, and dynamic mechanical properties of PBAT in PBAT/C30B nanocomposites. X-ray diffraction and transmission electron microscopy results indicated the formation of exfoliated nanocomposites at low clay loadings (<5 wt %) and a mixture of exfoliated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 46 publications
3
29
0
Order By: Relevance
“…The fillers can act as heterogeneous nucleation sites (Fig. 2), increasing the crystallinity of the PBAT [86,87]. The increase in crystallinity is usually associated with improved mechanical properties of the polymers [73,84,88,89], however, this relation is not always linear.…”
Section: Pbat-based Compositesmentioning
confidence: 99%
“…The fillers can act as heterogeneous nucleation sites (Fig. 2), increasing the crystallinity of the PBAT [86,87]. The increase in crystallinity is usually associated with improved mechanical properties of the polymers [73,84,88,89], however, this relation is not always linear.…”
Section: Pbat-based Compositesmentioning
confidence: 99%
“…In this context, the aliphatic polyesters have been the subject of increasing focus because of their biodegradability and biocompatibility [4][5][6]. Although these polyesters are biodegradable and renewable as well as edible, their industrial use is limited by their poor mechanical and water vapor barrier properties.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Yang et al [20] reported the elaboration of nano-biocomposites of PBAT and C30B by a solution-casting method. The effect of the clay loading on the crystallization behavior and physical properties of PBAT in PBAT/C30B nanocomposites was further investigated.…”
Section: Preparation Of Nano-biocomposites Based On Pbat Aliphatic-armentioning
confidence: 99%
“…In conclusion, the addition of finely dispersed C30B in the PBAT matrix had a significant influence on the spherulitic morphology and overall crystallization process of PBAT [20]. [20] The crystal structure of neat PBAT and PBAT/C30B nano-biocomposites with different clay loadings was investigated with WAXD.…”
Section: Preparation Of Nano-biocomposites Based On Pbat Aliphatic-armentioning
confidence: 99%
See 1 more Smart Citation